Integration Of Pjbl-Stem And Virtual Laboratory: A Strategy To Improve Critical Thinking Skills Of Prospective Elementary School Teachers - Fajri Basam; Hartono Bancong (Celebes Journal of Elementary Education, 2026)
This study investigated the effectiveness of integrating Project-Based Learning in Science, Technology, Engineering, and Mathematics (PjBL-STEM) with a virtual laboratory in enhancing the critical thinking skills of prospective elementary school teachers in physics-oriented science learning. The study employed a pre-experimental one-group pretest–posttest design involving 112 students from the Madrasah Ibtidaiyah Teacher Education Study Program at Universitas Islam Negeri Alauddin Makassar. Participants were selected through total sampling across three classes. Data were collected using a 10-item essay-based critical thinking test covering interpretation, analysis, and conclusion-drawing skills. The instrument demonstrated satisfactory validity (Aiken’s V ≥ 0.80) and reliability (Cronbach’s α ≥ 0.70). Data were analyzed using descriptive statistics and Hake’s normalized gain (N-Gain). The results showed substantial improvement in students’ critical thinking skills. While all participants were initially categorized as poor, posttest results indicated that 25% achieved excellent, 70% good, 2% fair, and only 4% remained poor. The mean N-Gain was 0.75, indicating a high level of improvement. High gains were also observed across all indicators: interpretation (0.77), analysis (0.71), and conclusion drawing (0.76). These findings suggest that PjBL-STEM integrated with virtual laboratories effectively promotes critical thinking and supports the development of 21st-century competencies among prospective elementary teachers.